Episcopal elections in the churches laws, practices, doctrines - Melloni, Alberto 1959-; Ruozzi, Federico 1981- (Brill, 2025)
"This work explores the procedures, norms, doctrines, and implications of episcopal elections in Christian churches. The evolution of episcopal elections reveals the political and social tensions and dynamics that influence the selection of bishops. The text analyses how such elections reflect the complexity of ecclesiastical structure from its origins in the New Testament to the present day. Election procedures never followed a fixed pattern, but were influenced by pre-existing traditions and contingent needs. The history of episcopal elections highlights the need for authority and consensus in the Christian community, exploring specific instances and historical developments that have shaped the current practice"--
Keywords: Bishops / Appointment, call, and election / History; Évêques / Nomination, choix et élection / Histoire